WHEN WORDS KILL: The transition from the paranoid-schizoid to the depressive position in psychotherapy. A case study. - Diderichsen, Birgitte (Psyke & Logos, 2022)
In the article I am presenting a single case study focusing on the patient’s speech. The patient is a 32 years old woman, suffering from a severe personality disorder. My purpose is to illustrate how the development from a fragmented speech to a coherent text corresponds to the development of relating to the object (the therapist), conceptualized as a development from the paranoid-schizoid to the depressive position.